2014
DOI: 10.1186/2193-1801-3-526
|View full text |Cite
|
Sign up to set email alerts
|

Significance of propolis administration for homeostasis of CD4+CD25+ immunoregulatory T cells controlling hyperglycemia

Abstract: In the present study, we examined the effect of ethanolic soluble derivative of propolis (EEP) extract on immunological function in diabetic mouse models with the aim of highlighting the role of regulatory T cell, the change of cell surface molecule, and in vivo productions of IFN-γ. Murine models of diabetes mellitus (DM) were created by injecting normal mice with S961 peptide. Normal BALB/c mice were injected intraperitoneally with peptide S961 300 mg/kg body weight (BW) twice a day for eight days. On day 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 32 publications
(53 reference statements)
1
41
0
1
Order By: Relevance
“…This finding contradicted previous research that found an increase of activated CD8 in diabetic mice compared to normal mice. 18 Possibly, our results showed a different tendency because we used an STZ injection method to induce the type 1 diabetic mouse model, while Rifa'i et al 18 used S961 peptide administration which resulted in type 2 diabetes. Furthermore, there is no explanation for the mechanism of how hyperglycemia could induce T-cell activation.…”
Section: Effect Of Hyperglycemia and Administration Of S Grandifloramentioning
confidence: 86%
See 2 more Smart Citations
“…This finding contradicted previous research that found an increase of activated CD8 in diabetic mice compared to normal mice. 18 Possibly, our results showed a different tendency because we used an STZ injection method to induce the type 1 diabetic mouse model, while Rifa'i et al 18 used S961 peptide administration which resulted in type 2 diabetes. Furthermore, there is no explanation for the mechanism of how hyperglycemia could induce T-cell activation.…”
Section: Effect Of Hyperglycemia and Administration Of S Grandifloramentioning
confidence: 86%
“…The supernatant was discarded, and the obtained pellet was subjected to intracellular staining with anti-mouse anti-IFN-γ, anti-mouse anti TNF-α and anti-mouse antiinterleukin-10 (IL-10) for 30 min. 18 …”
Section: Isolation Of Lymphoid Cells and Flow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Highly reactive T cells could induce insulin resistance by its proinflammatory action, but T regulatory cells can prevent this effect by producing IL-10 and TGF-β. This cells can also prevents inflammatory condition being wide-spread, by reversing the activated memory T cells become naive type [45].…”
Section: Vipalbumin ® Effect In Cd34 and Sdf-1 Mobilization In Streptmentioning
confidence: 99%
“…Another strategy also proposed to improve the healthy condition from diabetic patients with hyperglycemia by using propolis treatment [44]. This material is known to contain high-level of nutrient factor such as vitamins, polyphenols, and amino acids, that expected to improve insulin sensitvity and suppress the action of inflammatory molecules.…”
Section: Vipalbumin ® Effect In Cd34 and Sdf-1 Mobilization In Streptmentioning
confidence: 99%